Making space for mental health care within the penal estate. (March 2020) - Cassidy, Kathryn; Dyer, Wendy; Biddle, Paul; Brandon, Toby; McClelland, Norman; Ridley, Louise
Highlights: Prison authorities are developing new responses to care for prisoners with serious mental illnesses (SMIs) in the context of austerity. There is a shift away from externalising solutions for mental health care to transformation within the penal estate. Providers of mental health care in prisons should create small spaces, which are open to potentiality . Relative autonomy to establish different regimes of care-control enabled shifts in prisoner-staff relationships.